Their own agenda: The history, development, and culture of women's orchestras outside the united states - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”
https://doi.org/10.13016/M2QR4NT6S
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; discipline; femmes* musiciennes; genre; histoire des femmes*; histoire et politique; inégalités; musique; mémoires/thèses; périodes historiques; ressource en ligne; systèmes d'oppression; thématiques

Territoires de libération : perspectives féministes musulmanes - Benhadjoudja, Leïla (Tumultes, 2018)
Keywords: 2000-2029; 2010-2019; amériques; approches et analyses; corps; discipline; discours dominant; fem3400; féminisme islamique; féminisme musulman; histoire et politique; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppression; thématiques

Les représentations médiatiques des femmes aux élections municipales et la politique vue par les journaux étudiants universitaires québécois: des représentations genrées et équilibrées - Bourassa-Dansereau, Caterine; Lalancette, Mireille; Morin, Laurence; Rouillard, Carol-Anne; Table de concertation des groupes de femmes de la Montérégie; Théberge-Guyon, Marianne (Service aux collectivités de l'UQAM/Table de concertation des groupes de femmes du Bas St-Laurent/Tables de concertation des groupes de femmes de la Montérégie/Table de concertation du mouvement des femmes de la Mauricie, 2018)
Sommaire des rapports produits dans le cadre du projet « Plus de femmes en politique. Les médias et les instances municipales, des acteurs-clés! »
Keywords: 2000-2029; 2010-2019; SAC; citoyenneté; femmes*; histoire et politique; politique; périodes historiques; recherche partenariale; recherche-milieux de pratique; ressource en ligne; thématiques